The Natural History of Trisomy 21: Outcome Data From a Large Tertiary Referral Centre. Issue 4 (April 2022) - O'Connor, Clare; Moore, Rebecca; McParland, Peter; Hughes, Heather; Cathcart, Barbara; Higgins, Shane; Mahony, Rhona; Carroll, Steve; Walsh, Jennifer; McAuliffe, Fionnuala
Abstract : (Abstracted from Fetal Diagn Ther 2021;48:575–581) Down syndrome (DS) or trisomy 21 (T21) is characterized as the presence of a third copy of chromosome 21. The rate of DS increases with maternal age, and it is the most common aneuploidy in live-born infants.